Serum vitamin D levels are inversely related with non‐alcoholic fatty liver disease independent of visceral obesity in Chinese postmenopausal women. (February 2015) - Lu, Zhigang; Pan, Xiaoping; Hu, Yaqin; Hao, Yaping; Luo, Yuqi; Hu, Xiang; Ma, Xiaojing; Bao, Yuqian; Jia, Weiping
Summary The aim of the present study was to investigate the association between serum vitamin D levels and both visceral adipose and with non‐alcoholic fatty liver disease (NAFLD) in Chinese postmenopausal women. Four hundred and fifty‐one postmenopausal women between 45 and 74 years of age (mean (± SD) age 57.3 ± 4.6 years) were enrolled in the study. All subjects participated in the Shanghai Obesity Study between June and August 2011 and underwent abdominal magnetic resonance imaging and an abdominal ultrasonography. Patients with a visceral fat area (VFA) ≥ 80 cm2 were classified as abdominally obese. Serum 25‐hydroxyvitamin D3 (25(OH)D3) levels were measured with an electrochemiluminescence immunoassay. The prevalence of NAFLD in the study population was 34.8% (n = 157). Women with abdominal obesity had significantly lower serum 25(OH)D3 levels than those without abdominal obesity (median (interquartile range) 11.23 (8.64–14.12) vs 12.56 (9.41–15.98) ng/mL, respectively; P < 0.01). Regardless of abdominal obesity status, serum 25(OH)D3 levels in patients with NAFLD were lower than those without non‐NAFLD (11.14 (8.63–13.81) vs 12.92 (9.48–16.37) ng/mL (P < 0.05) for those without abdominal obesity; 10.86 (8.61–13.56) vs 11.55 (8.82–16.38) ng/mL (P < 0.05) for those with abdominal obesity). Partial correlation analyses demonstrated a negative correlation between serum 25(OH)D3 levels and VFA (P < 0.05). Logistic regression analysis revealed that high serum 25(OH)D3 levels were a protective factor against NAFLD after adjusting for risk factors such as VFA. In conclusion, independent of visceral obesity, vitamin D is inversely correlated with NAFLD in Chinese postmenopausal women.